2014
DOI: 10.1371/journal.pone.0097128
|View full text |Cite
|
Sign up to set email alerts
|

A Diplodocid Sauropod Survivor from the Early Cretaceous of South America

Abstract: Diplodocids are by far the most emblematic sauropod dinosaurs. They are part of Diplodocoidea, a vast clade whose other members are well-known from Jurassic and Cretaceous strata in Africa, Europe, North and South America. However, Diplodocids were never certainly recognized from the Cretaceous or in any other southern land mass besides Africa. Here we report a new sauropod, Leikupal laticauda gen. et sp. nov., from the early Lower Cretaceous (Bajada Colorada Formation) of Neuquén Province, Patagonia, Argentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 47 publications
3
60
0
3
Order By: Relevance
“…5) and Leinkupal (Gallina et al, 2014) also show anteriorly curved anterior caudal ribs, but only in the Late Cretaceous Chinese titanosaur Xianshanosaurus is this as strongly developed as in Wamweracaudia (Lü et al, 2009;; as such, this feature is regarded as an autapomorphy of Wamweracaudia (see also 'Discussion: Turiasaurs outside of Euamerica?'). Although the caudal rib is deflected ventrally, it contrasts with the condition in diplodocids whereby the distal tip of the rib projects ventrally, giving the ventral margin a concave profile in anterior/posterior view (Gallina et al, 2014). As in Cd XXX, the caudal rib has a dorsoventrally concave anterior surface and dorsoventrally convex posterior surface.…”
Section: Description and Comparisons Of Holotype Materials Of Wamweracmentioning
confidence: 99%
“…5) and Leinkupal (Gallina et al, 2014) also show anteriorly curved anterior caudal ribs, but only in the Late Cretaceous Chinese titanosaur Xianshanosaurus is this as strongly developed as in Wamweracaudia (Lü et al, 2009;; as such, this feature is regarded as an autapomorphy of Wamweracaudia (see also 'Discussion: Turiasaurs outside of Euamerica?'). Although the caudal rib is deflected ventrally, it contrasts with the condition in diplodocids whereby the distal tip of the rib projects ventrally, giving the ventral margin a concave profile in anterior/posterior view (Gallina et al, 2014). As in Cd XXX, the caudal rib has a dorsoventrally concave anterior surface and dorsoventrally convex posterior surface.…”
Section: Description and Comparisons Of Holotype Materials Of Wamweracmentioning
confidence: 99%
“…Cretaceous brachiosaurid diversity appears to have plummeted (or even reduced to zero) outside of North America (D'Emic, 2012; Mannion et al, 2013) and Africa (McPhee et al, 2016), although the clade possibly expanded into the northern tip of South America (Carballido et al, 2015), whilst Somphospondyli experienced a global radiation (D'Emic, 2012;Mannion et al, 2013). Within the narrow-toothed Diplodocoidea, diplodocids were thought to have gone extinct at the J/K boundary , although recent discoveries in the earliest Cretaceous of Africa (McPhee et al, 2016) and South America (Gallina et al, 2014) indicate that at least one diplodocid lineage survived. Cretaceous dicraeosaurid diplodocoids are also known only from South America (Salgado & Bonaparte, 1991) and Africa (McPhee et al, 2016), whereas rebbachisaurids diversified in northern Africa, Europe and South America in the Early Cretaceous (Carballido et al, 2012).…”
Section: (3) Vertebrates (A) Dinosaursmentioning
confidence: 99%
“…For example, there is a seemingly selective extinction of larger-sized dinosaurs (sauropods and theropods) across the J/K boundary Zanno & Makovicky, 2013;Cobos et al, 2014;De Souza & Santucci, 2014;Carballido et al, 2015). In sauropods, this extinction is focused on broad-toothed non-neosauropod eusauropods and narrow-toothed diplodocids , with just two occurrences known from the Cretaceous (Gallina et al, 2014;McPhee et al, 2016), and is followed by the diversification of rebbachisaurids and titanosauriforms . The earliest Cretaceous therefore represented a 'transitional' phase in sauropod evolution (Upchurch et al, 2015b), a pattern also found in Asia, with the replacement of non-neosauropods by titanosauriforms across the J/K boundary (Wilson & Upchurch, 2009;Mannion et al, 2013).…”
Section: (C) Additional Environmental Changes That Require Explorationmentioning
confidence: 99%
“…Este único espécimen se halla compuesto por una escápula incompleta y porciones de fémur y fíbula. advirtió en él ciertas similitudes con Rebbachisaurus garasbae, en cuanto a la morfología de la escápula, por lo que propuso una nueva familia de saurópodos, los Rebbachisauridae (Bonaparte, 1997), el taxón hermano de Dicraeosauridae y Diplodocidae, con una distribución temporal puramente cretácica Whitlock, 2011 permiten asignarlo a la familia Diplodocidae, constituyendo el registro más moderno para este grupo y el primero para Sudamérica (Gallina et al, 2014b).…”
Section: Acknowledgmentsunclassified